Rs2072135, a low‐penetrance variant for chronic lymphocytic leukaemia?. (14th May 2013) - Sava, Georgina P.; Speedy, Helen E.; Di, Maria Chiara; Deaglio, Silvia; Karabon, Lidia; Frydecka, Irena; Woszczyk, Dariusz; Rossi, Davide; Gaidano, Gianluca; Mansouri, Larry; Smedby, Karin E.; Juliusson, Gunnar; et al.
Summary Recent multi‐stage genome‐wide association studies (GWAS) have identified single nucleotide polymorphisms (SNPs) that are robustly associated with chronic lymphocytic leukaemia (CLL) risk. Given that most of these SNPs map to non‐coding regions of the genome, it suggests that the functional basis of many GWAS signals will be through differential gene expression. By referencing publically accessible expression quantitative trait loci (eQTL) data on lymphoblastoid cells lines (LCLs) we have globally demonstrated an association between GWAS P‐values and eQTLs, consistent with much of the variation in CLL risk being defined by variants impacting on gene expression. To explore using eQTL data to select GWAS SNPs for replication, we genotyped rs2072135 (GWAS P‐value = 0·0024, eQTL P‐value = 1·510−19) in five independent case‐control series totalling 1968 cases and 3538 controls. While not attaining statistical significance (combined P‐value = 1 × 10−4), rs2072135 defines a promising risk locus for CLL. Incorporating eQTL information offers an attractive strategy for selecting SNPs from GWAS for validation.